Obesity and Spine Surgery: A Qualitative Review About Outcomes and Complications. Is It Time for New Perspectives on Future Researches?. Issue 6 (July 2022) - Cofano, Fabio; Perna, Giuseppe Di; Bongiovanni, Daria; Roscigno, Vittoria; Baldassarre, Bianca Maria; Petrone, Salvatore; Tartara, Fulvio; Garbossa, Diego; Bozzaro, Marco
Study Design: Literature review. Objectives: An increasing number of obese patients requires operative care for degenerative spinal disorders. The aim of this review is to analyze the available evidence regarding the role of obesity on outcomes after spine surgery. Peri-operative complications and clinical results are evaluated for both cervical and lumbar surgery. Furthermore, the contribution of MIS techniques for lumbar surgery to play a role in reducing risks has been analyzed. Methods: Only articles published in English in the last 10 years were reviewed. Inclusion criteria of the references were based on the scope of this review, according to PRISMA guidelines. Moreover, only paper analyzing obesity-related complications in spine surgery have been selected and thoroughly reviewed. Each article was classified according to its rating of evidence using the Sacket Grading System. Results: A total number of 1636 articles were found, but only 130 of them were considered to be relevant after thorough evaluation and according to PRISMA checklist. The majority of the included papers were classified according to the Sacket Grading System as Level 2 (Retrospective Studies). Conclusion: Evidence suggest that obese patients could benefit from spine surgery and outcomes be satisfactory. A higher rate of peri-operative complications is reported among obese patients, especially in posterior approaches. The use of MIS techniques plays a key role in order to reduce surgical risks. Further studies should evaluate the role of multidisciplinary counseling between spine surgeons, nutritionists and bariatric surgeons, in order to plan proper weight loss before elective spine surgery.